Perkembangan Islam di Turki Menerusi Pendekatan Politik: Satu Sorotan Sejarah: The Development of Islam in Turkey through Political Approach: A Historical Review - Ibrahim, Muhammad Khalis; Mohd Nor, Mohd Roslan (Online Journal of Research in Islamic Studies, 2018)
Mustafa Kemal Atatürk built a modern Turkish state through secularization approach. Atatürk’s reform program which continued by Kemalist regime triggered reactions among those who aimed to bring back Islam to its place. This paper focuses on the historical review of the development of Islam in Turkey through the political approach during early phases, namely during Adnan Menderes and Necmettin Erbakan era. The methodology of this study involved content analysis method and comparative method on related sources. Generally, Menderes and Erbakan played their roles while on power for the development of Islam in Turkey eventhough there were some limitations. Other than political entities which carried out pro-Islamic policies, the Turkish people who were siding to Islam also contributed to the development of Islam in Turkey indirectly.